SITUS WEB GEREJA KEMAH INJIL INDONESIA (GKII) EL SHADAI AMBAN MANOKWARI PAPUA BARAT DENGAN MENGGUNAKAN FRAMEWORK CODEIGNITER: WEBSITE OF EL SHADAI AMBAN MANOKWARI INDONESIAN GOSPEL TENT CHURCH (IGTC) WEST PAPUA USING THE CODEIGNITER FRAMEWORK - Ogelyn Miranda Sabandar; Julius Panda Putra Naibaho; Nur Jamila (JISTECH: Journal of Information Science and Technology, 2023)
Website is a whole web page that contains very large information contained in a domain. Information on the web is presented in a web page. The church is an organization. Church by conveying various information, both the schedule and the work program of the governing body to the news of the congregation. In this case the process of conveying information is still in the form of bulletins that are printed out. Therefore, a website design was created that can help store worship schedule data, activities and information from the church. The design of the Indonesian Bible Tabernacle Church Website design uses the waterfall method and is built using the codeigniter framework. This designed church website consists of 2 actors, namely user and admin. This website has several menu pages, namely Home, Church Profile, Announcement, Documentation and Contact. The final stage of making this church website is testing the website using the black box testing method and conducting a survey by distributing questionnaires to website users to be able to find out the level of satisfaction with the website.